Public Legitimacy of Government and People’s Political Participation: The Case of the 2020 West Sumatra Regional Election, Indonesia - Agung Marsallindo; Cici Safitri (Journal of Asian Social Science Research, 2021)
West Sumatra is one of the Indonesian provinces that conducted the simultaneous regional elections in 2020. It was said that it had the highest rate of election vulnerability index in 2020 based on the indicators of assessment including political participation, socio-political context, free and fair elections, contest, and vulnerability due to the Covid-19 Pandemic. In West Sumatra, the three regional head elections in 2005, 2010, and 2015 show that public political participation decreased from 64% to 58%. However, in the 2020 election, the voter turnout rate rose to 61.68%. Therefore, this article analyzes how did the West Sumatra government build public legitimacy to increase public political participation in the 2020 election, which was held in the Covid-19 Pandemic with all its limitations? In doing so, it uses a literature study method. The collected data were analyzed according to the principles of the qualitative method. The results of this study indicate that public legitimacy of the 2020 regional election in West Sumatra was built by three actors in the consolidation of democracy in the gubernatorial election as follows: a) local government, b) election participants and c) election management institutions, each of which had strategic steps in restoring public trust in the election during the Covid-19 Pandemic.